Improving Surface Strip Adjustment Accuracy Using the Point-to-Plane Iterative Closest Point (ICP) - Maharani, Monica; Arif, Riyas Syamsul (Program Studi Teknik Geomatika Fakultas Teknologi Mineral Universitas Pembangunan Nasional, 2025)
This study aims to evaluate the effectiveness of the point-to-plane method for LiDAR point cloud data registration, especially for strip adjustment applications. Using two different LiDAR scenes with varying land cover, a comparative analysis was conducted between the point-to-plane method and the conventional point-to-point method. The performance of the point-to-plane method was assessed based on Root Mean Square Error (RMSE), transformation matrix accuracy, fitness, correspondence, and visual observation. The results show that the point-to-plane method consistently outperforms the point-to-point approach, by producing significantly lower RMSE values, more accurate transformation matrices, and higher fitness scores across all land cover types. This study validates that point-to-plane ICP is capable of providing more robust and accurate results for topographic data registration, and offers improvements to high-precision geospatial applications.